CONDITION STUDY SHIPPING DURING THE PANDEMIC (Transport systems and technologies, 2021)
Today, humanity has faced a fundamentally new catastrophe - the Covid-19 pandemic. Quarantine, closing borders, creating numerous problems for almost all states - all these are the realities of today. Experts will still be able to fully assess the scale of the economic shock associated with the epidemic and all its long-term consequences. But it is already clear that the recovery of the global economy is not an easy one. And already tested anti-crisis measures will not always work. It is necessary to look for fundamentally new, non-standard solutions. The aim of the research is to analyze the state of trade against the background of the global world economic situation. Identify the shortcomings of the industry, development prospects and highlight the economic benefits that need to be addressed as a matter of priority in order to improve performance and improve the situation during a pandemic. The article examines the current state of the global economic situation in the maritime transport industry during the Covid-19 pandemic. The international market of maritime trade is based on certain patterns, among which there is a clear focus on the parameters of international economic relations, the constant use of innovative technologies and the cyclical changes in key indicators. The trend of development of the maritime transport industry and its regionalization is due to a complex set of external and internal factors. Therefore, the article considers the relationship and impact of both negative and positive factors on the state of the world economy. The data of the interim economic forecasts for 2019-2022 in the estimated comparison of countries that have a global impact on the economic development of partner countries are studied. The interrelation of economic and maritime industries is analyzed, the state of modern problems of sea transportation is investigated, perspective directions are revealed and the necessity of concrete decisions for large-scale development of competitiveness of the transport industry is emphasized. As a result of the research it is suggested: in order to automate the process of sea transportation to accelerate the introduction of contactless document management, to consolidate the position of maritime logistics, which plays an important organizational and cost-effective role in modern economic relations and trade flows.
Keywords: economic crisis; the Covid-19 pandemic; maritime logistics; commodity circulation; sea transportation.